Bu Shen Huo Xue decoction promotes functional recovery in spinal cord injury mice by improving the microenvironment to promote axonal regeneration - Yonghui Hou; Dan Luo; Yu Hou; Jiyao Luan; Jiheng Zhan; Zepeng Chen; Shunmei E; Liangliang Xu; Dingkun Lin (BMC, 2022)
Abstract Background Bu-Shen-Huo-Xue (BSHX) decoction has been used in the postoperative rehabilitation of patients with spinal cord injury in China. In the present study, we aim to reveal the bioactive compounds in BSHX decoction and comprehensively explore the effects of BSHX decoction and the underlying mechanism in spinal cord injury recovery. Methods The main chemical constituents in BSHX decoction were determined by UPLC-MS/MS. SCI mice were induced by a pneumatic impact device at T9-T10 level of the vertebra, and treated with BSHX decoction. Basso-Beattie-Bresnahan (BBB) score, footprint analysis, hematoxylin-eosin (H&E) staining, Nissl staining and a series of immunofluorescence staining were performed to investigate the functional recovery, glial scar formation and axon regeneration after BSHX treatment. Immunofluorescent staining of bromodeoxyuridine (BrdU), neuronal nuclei (NeuN) and glial fibrillary acidic protein (GFAP) was performed to evaluate the effect of BSHX decoction on neural stem cells (NSCs) proliferation and differentiation. Results We found that the main compounds in BSHX decoction were Gallic acid, 3,4-Dihydroxybenzaldehyde, (+)-Catechin, Paeoniflorin, Rosmarinic acid, and Diosmetin. BSHX decoction improved the pathological findings in SCI mice through invigorating blood circulation and cleaning blood stasis in the lesion site. In addition, it reduced tissue damage and neuron loss by inhibiting astrocytes activation, and promoting the polarization of microglia towards M2 phenotype. The functional recovery test revealed that BSHX treatment improved the motor function recovery post SCI. Conclusions Our study provided evidence that BSHX treatment could improve the microenvironment of the injured spinal cord to promote axonal regeneration and functional recovery in SCI mice.